Association analysis of miRNA-related genetic polymorphisms in miR-143/145 and KRAS with colorectal cancer susceptibility and survival. Issue 4 (30th April 2021) - Wang, Danyang; Liu, Qingmin; Ren, Yanjun; Zhang, Yan; Wang, Xin; Liu, Bing
Abstract: Background: There is accumulating evidence of aberrant expression of miR-143 and miR-145 and their target gene KRAS in colorectal cancer (CRC). We hypothesize that single nucleotide polymorphisms (SNPs) within or near mRNA–microRNA (miRNA) binding sites may affect miRNA/target gene interaction, resulting in differential mRNA/protein expression and promoting the development and progression of CRC. Methods: We conducted a case–control study of 507 patients with CRC recruited from a tertiary hospital and 497 population-based controls to assess the association of genetic polymorphisms in miR-143/145 and the KRAS 3′ untranslated region (3′UTR) with susceptibility to CRC and patients' survival. In addition, genetic variations of genomic regions located from 500 bp upstream to 500 bp downstream of the miR-143/miR-145 gene and the 3′UTR of KRAS were selected for analysis using the Haploview and HaploReg software. Results: Using publicly available expression profiling data, we found that miR-143/145 and KRAS expression were all reduced in rectal cancer tissue compared with adjacent non-neoplastic large intestinal mucosa. The rs74693964 C/T variant located 65 bp downstream of miR-145 genomic regions was observed to be associated with susceptibility to CRC (adjusted odds ratio (OR): 2.414, 95% CI: 1.385–4.206). Cumulative effects of miR-143 and miR-145 on CRC risk were observed ( P trend =0.03). Patients having CRC carrying variant genotype TT of KRAS rs712 had poorer survival (log-rank P =0.044, adjusted hazard ratio (HR): 4.328, 95% CI: 1.236–15.147). Conclusions: Our results indicate that miRNA-related polymorphisms in miR-143/145 and KRAS are likely to be deleterious and represent potential biomarkers for susceptibility to CRC and patients' survival.